Indev Model sebagai Pilihan Diversi Terhadap Anak yang Berhadapan dengan Hukum - Nurul Huda (Wacana Hukum, 2019)
Diversion is the transfer of the settlement of a Children's case from the criminal justice process to the process outside of criminal justice. The provision of diversion in the Law on the Juvenile Justice System, can only be applied to criminal offenses under sentence of imprisonment under 7 (seven) years in prison. The diversion model, based on the Juvenile Justice System Law, does not protect children if there are cases of sexual violence with child offenders and child victims. Based on research, the police with discretionary authority can apply the Indev Model. If applying the Indev Model, the parties forget the legal framework, and assume that a case is an interpersonal conflict, not a legal conflict. So that efforts to protect child offenders and victims of sexual violence can be realized through the Indev Model.